UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN BUAS-BUAS (Premna serratifolia L.) ASAL KABUPATEN MELAWI PROVINSI KALIMANTAN BARAT DENGAN METODE DPPH - Weni Puspita; Dina Yuspita Sari; Ika Ristia Rahman (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Buas Buas (Premna serratifolia L.) contains secondary metabolites of flavonoids, saponins, tannins and triterpenoids/steroids, where flavonoids are known to have antioxidant properties and counteract free radicals. Antioxidants are compounds that can fight toxic hazards and reduce cell damage to the body caused by free radical oxidation. The purpose of this study was to determine the antioxidant activity of ethanol extracts of buas-buas leaves was carried out by DPPH (2,2-diphenyl-1-picrylhydrazyl), using UV-Vis spectrophotometry at wavelength 518.40 nm with various concentrations of 10 ppm, 20 ppm, 30 ppm, 40 ppm and 50 ppm. The results showed that Buas Buas leaves (Premna serratifolia L.) had an antioxidant activity with IC50 values ??of 20.66 ug / mL.